2001
DOI: 10.1289/ehp.01109965
|View full text |Cite
|
Sign up to set email alerts
|

Combustion products of 1,3-butadiene are cytotoxic and genotoxic to human bronchial epithelial cells.

Abstract: Adverse health effects of airborne toxicants, especially small respirable particles and their associated adsorbed chemicals, are of growing concern to health professionals, governmental agencies, and the general public. Areas rich in petrochemical processing facilities (e.g., eastern Texas and southern California) chronically have poor air quality. Atmospheric releases of products of incomplete combustion (e.g., soot) from these facilities are not subject to rigorous regulatory enforcement. Although soot can i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 24 publications
1
20
1
Order By: Relevance
“…Previously, we reported that extranuclear fluorescence was detected within 4 h after exposure of NHBE cells to BSDE and that the fluorescence intensified up to 24 h (Catallo et al 2001). In order to establish that BSEE also causes extranuclear fluorescence, BEAS-2B cells exposed to either a vehicle control (DMSO or EtOH) or toxicant mixture (BSDE or BSEE) were visualized 6, 24, 48, and 72 h after exposure.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Previously, we reported that extranuclear fluorescence was detected within 4 h after exposure of NHBE cells to BSDE and that the fluorescence intensified up to 24 h (Catallo et al 2001). In order to establish that BSEE also causes extranuclear fluorescence, BEAS-2B cells exposed to either a vehicle control (DMSO or EtOH) or toxicant mixture (BSDE or BSEE) were visualized 6, 24, 48, and 72 h after exposure.…”
Section: Resultsmentioning
confidence: 96%
“…Based on the oxidizing potential of BDS (Catallo et al 2001), we believed that these particles would oxidize proteins in cells. If this is the case, then BDS would be expected to inhibit the activity of enzymes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations